2009
DOI: 10.1177/0022219409345014
|View full text |Cite
|
Sign up to set email alerts
|

Recognition, Expression, and Understanding Facial Expressions of Emotion in Adolescents With Nonverbal and General Learning Disabilities

Abstract: Children with nonverbal learning disabilities (NVLD) have been found to be worse at recognizing facial expressions than children with verbal learning disabilities (LD) and without LD. However, little research has been done with adolescents. In addition, expressing and understanding facial expressions is yet to be studied among adolescents with LD subtypes. This study examined abilities of adolescents with NVLD, with general learning disabilities (GLD), and without LD to recognize, express, and understand facia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 121 publications
(427 reference statements)
2
30
0
2
Order By: Relevance
“…Surprisingly, among the over 14 000 journal papers, only 237 papers were identified when the category filter was set to education related. These papers included studies on topics such as modeling human emotions in educational computer games (eg, Visschedijk, Lazonder, van der Hulst, Vink & Leemkuil, ) and the recognition of facial expressions among students with learning disabilities (eg, Bloom & Heath, ).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, among the over 14 000 journal papers, only 237 papers were identified when the category filter was set to education related. These papers included studies on topics such as modeling human emotions in educational computer games (eg, Visschedijk, Lazonder, van der Hulst, Vink & Leemkuil, ) and the recognition of facial expressions among students with learning disabilities (eg, Bloom & Heath, ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of qualitative measures, such as interviews, has been useful in helping researchers demonstrate the positive impact of social skill interventions among students with LDs (Gresham et al 2004;Maag 2005). Because the content and goals of these trainings have varied throughout the literature (Bloom and Heath 2010;Schnizer et al 2007), however, cohesive claims regarding the general impact of "social skill training" for students with LDs are elusive.…”
Section: Research On Interventions For Students With Ldsmentioning
confidence: 99%
“…The verbal/performance IQ (VIQ/PIQ) discrepancy initially used to screen for NLD (Rourke et al, 1971; Rourke & Telegdy, 1971) was suggested to be a less clear indicator in younger children (Rourke et al, 1973) and may occur in fewer than one third of older children identified as having NLD (Drummond, Ahmad, & Rourke, 2005; Pelletier, Ahmad, & Rourke, 2001). Nonetheless, diagnostic criteria defined by Rourke and colleagues, often including a VIQ/PIQ discrepancy, are still widely used in studies of the NLD population (Bloom & Heath, 2010; Forrest, 2004; Galway & Metsala, 2011; Keller, Tillery, & McFadden, 2006; Petti et al, 2003; Semrud-Clikeman, Walkowiak, Wilkinson, & Christopher, 2010). …”
Section: Nldmentioning
confidence: 99%